Effect of Gelling Agent Type on the Physical Properties of Nanoemulsion-Based Gels - Arancibia-Aguilar, C; Riquelme-Hinojosa, N (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Senior populations may experience nutritional deficiencies due to physiological changes that occur during aging, such as swallowing disorders, where easy-to-swallow foods are required to increase comfort during food consumption. In this context, the design of nanoemulsion-based gels (NBGs) can be an alternative for satisfying the textural requirements of seniors. This article aimed to develop NBGs with different gelling agents, evaluating their physical properties. NBGs were prepared with a base nanoemulsion (d = 188 nm) and carrageenan (CA) or agar (AG) at two concentrations (0.5–1.5% w/w). The color, rheology, texture, water-holding capacity (WHC) and FT-IR spectra were determined. The results showed that the CA-based gels were more yellow than the AG ones, with the highest hydrocolloid concentration. All gels showed a non-Newtonian flow behavior, where the gels’ consistency and shear-thinning behavior increased with the hydrocolloid concentration. Furthermore, elastic behavior predominated over viscous behavior in all the gels, being more pronounced in those with AG. Similarly, all the gels presented low values of textural parameters, indicating an adequate texture for seniors. The FT-IR spectra revealed non-covalent interactions between nanoemulsions and hydrocolloids, independent of their type and concentration. Finally, the CA-based gels presented a higher WHC than the AG ones. Therefore, NBG physical properties can be modulated according to gelling agent type in order to design foods adapted for seniors. © 2023 by the authors.